Role of intracellular calcium in fast and slow desensitization of P(2)-receptors in PC12 cells - Khiroug, L (1997)
1. Combined whole-cell patch clamp recording and confocal laser scanning microscopy of [Ca(2+)](i) transients were performed on single PC12 cells to study any correlation between membrane currents induced by ATP and elevation in [Ca(2+)](i). ATP was applied by pressure from micropipettes near the recorded PC12 cells continuously superfused at a fast rate. 2. Brief (20 ms) pulses of ATP elicited monophasic inward currents and [Ca(2+)](i) increases. Long applications (2 s) of ATP (5 mM) evoked peak currents which rapidly faded during the pulse and were followed by a large rebound current, interpreted as due to rapid desensitization and recovery of P(2)- receptors. The associated [Ca(2+)](i) increase grew monotonically to a peak reached only after the occurrence of the current rebound, indicating that it is unlikely this cation has a role in fast desensitization. 3. Both membrane currents and [Ca(2+)](i) transients were linearly dependent on holding membrane potential, suggesting that Ca(2+) influx is the predominant cause of [Ca(2+)](i) elevation. This view was supported by experiments carried out in Ca(2+)-free solution. 4. Brief pulses of ATP applied after a desensitizing pulse (2 s) of the same elicited smaller inward currents and [Ca(2+)](i) rises indicating a role for [Ca(2+)](i) in controlling slow desensitization of P(2)-receptors. 5. This notion was confirmed in experiments with various [Ca(2+)](i) chelators which differentially affected slow desensitization in relation to their buffering capacity, while sparing fast receptor desensitization. 6. These results suggest a role for [Ca(2+)](i) in slow rather than fast desensitization of P(2)-receptors, thus proposing this divalent cation as an intracellular factor able to provide an efficient and reversible control over receptor activity induced by ATP.